Certainty and Legal Protection for the Purchase of Auction Goods - Sarikun Sarikun; Ekawati Ekawati; Gusti Heliana Safitri; Benhard Kurniawan Pasaribu; Heribertus Richard Carsarino; Dina Paramitha Hefni Putri (Journal Of Social Science (JoSS), 2024)
An auction is a form of creative buying and selling transaction, where one party commits to give up ownership of goods and the other party agrees to pay the agreed price. This research aims to analyze the legal certainty and protection given to buyers of auction goods, as well as to understand how the auction mechanism can protect the rights of buyers from third party claims. This research uses a normative juridical approach, namely assessing and evaluating formal legal regulations relating to auctions. This method is carried out by analyzing positive legal norms and regulations governing the auction process in Indonesia. The results showed that legal protection for auction buyers is guaranteed through provisions in the Auction Regulations which state that goods purchased through auctions are free from third party claims. Auction buyers have absolute rights to the auction goods they buy, which can be defended from the demands of any party. Preventive legal protection is guaranteed by applicable regulations, which provide legal evidence in the form of auction minutes as the basis for the transfer of ownership rights. This is important to reduce legal risks and ensure fairness in auction transactions. Legal certainty for auction buyers is essential to ensure that the goods purchased are protected from third-party claims